INVESTIGATION OF THE EFFECT OF COMPETENCY ASSESSMENT PROCESSES ON AIRCRAFT MAINTENANCE TECHNICIAN - GÜNEŞ, Tarık; TURHAN, Uğur; AÇIKEL, Birsen (International Sustainable Aviation Research Society, 2019)
ABSTRACT Aircraft maintenance activities are one of the most important criteria for the safe and effective execution of aviation operations. In aircraft accidents and incidents, maintenance factor is vital for the development of safety for organizations, authorities and countries in the aviation field. Effective maintenance activities will also contribute to the costs of organizations by ensuring the safe operations of aircraft with people. Maintenance activities are carried out by maintenance technicians in areas such as hangars or aprons. Aircraft maintenance technicians' performance in performing maintenance activities directly impacts flight safety and technician safety, which in turn has a positive or negative impact on organizations. Improving technician competency assessment processes can reduce maintenance errors, improve technician performance, create positive impacts on safe and efficient flight operations, reduce maintenance costs and benefit of entire aviation industry. Technician competency should be considered in performance evaluations and assignments by assessing in all levels with the compatibility of videly used human resources management methods. In this study, technician competence assessment processes are mentioned, the effects of these processes on aviation safety are explained and solutions are proposed to develop and apply the assessment processes. Keywords: Aircraft maintenance, aircraft maintenance technician competency, competency assessment, human factors in aviation.
Keywords: 2. Zero hunger